Technical re-equipment of the molding shop of the foundry based on the introduction of impulse molding - Лаврова, Надежда Игоревна (Technology audit and production reserves, 2013)
As the analysis of the state of foundry shops shows, one of the "bottlenecks" are molding shops, but the main problem in these shops is the wear of molding equipment. Therefore, the studies on the development of measures for the reconstruction of the molding equipment, considering it as a part of the technical re-equipment of the molding shop of the foundry, are relevant. As a result of the conducted research on the issues of planning and organization of measures on technical re-equipment, providing the possibility of reducing the deadlines and rational allocation of resources in the process of technical re-equipment of the molding shop of the foundry, the activity network on the implementation of the complex of works on the technical re-equipment was built. The essence of technical re-equipment is the replacement of obsolete jolt-squeeze molding machines by modern impulse molding machines. It was found that the most important operations in carrying out the preparatory works are the reconstruction of the system of machine drives, development of technological schemes of mounting, construction works on the preparation and mounting of drives, mounting of prefabricated elements of equipment, preparation for the mounting of the main technological equipment. The most important operations when carrying out mounting are operations of mounting of the frame of cylinders and pressing mechanism. The application of the described solutions can be used in the process of technical re-equipment of molding shops of the foundry.